Multi-keyword searchable encryption scheme based on dynamic cuckoo filter - WANG Qian; ZHAO Shengnan; ZHAO Chuan; JING Shan; CHEN Zhenxiang (Tongxin xuebao)
Existing solutions have utilized Cuckoo Filter (CF) on the server side to achieve multi-keyword searching.The capacity of CF is preset, which can not satisfy the continuous growth of the capacity expansion demand on the server side. To solve the above problems, a dynamic multi-keyword searchable encryption (DMKSE) was proposed, which used the dynamic cuckoo filter to solve the server-side capacity expansion demand, and improved the storage of document-keyword pairs, which improved the space utilization of the server-side, without additional time overhead. Experimental results show that DMKSE improves space utilization by at least 1.3481 times over the original scheme.